Redescription of the genus Coniceps Loew, 1873 (Diptera, Richardiidae) - Wendt, Lisiane Dilli; Ale-Rocha, Rosaly (Zootaxa, 2012)
The genus Coniceps Loew is restricted to the central and southern part of the continental United States of America, andcontains a single species, C. niger Loew, 1873. A redescription of the type species of the genus including illustrations ofmain external characters and the first illustrations of male and female terminalia are provided. The lectotype and paralec-totypes are designated. A brief discussion on the superficial similarities between Coniceps and the Neotropical Ozaenina Enderlein is also provided.